Estimasi Karbon pada Tegakan Kopi di Lahan Agroforestri Desa Pandansari Kecamatan Poncokusumo Kabupaten Malang - Najih, Riyan Riyadlun; Hakim, Luchman; Zayadi, Hasan (FMIPA UNISMA, 2021)
The agroforestry system is a solution offered so that the forest area does not decrease due to forest destruction and the environment is able to perform its function, namely as a carbon storage. This study was aimed to determine the potential for carbon stored in coffee stands and abiotic factors in coffee stands on agroforestry land. Samples by purposive sampling stand samples of Coffeaarabica, Coffea canephora, and Coffea liberica as many as 20 trees with a total sample of 60 stands. the abiotic factor was measured at three representative points. Data obtained in the form of dbh (Â±1,3 m), type of coffee, plant age, wood dencity, abiotic factor data, biomass, and carbon. Data analysis included tree biomass data with the allometric formula Ketterings dry weight = 0.11 Ï D2.62 (2001) andÂ allometric formula Arifin dry weight = 0.281 D2.0635 (2001). Data analysis included carbon biomass = dry weight x 0.47. The results showed that the largest carbon storage was in Coffea liberica, then Coffea canephora and the smallest carbon storage was in Coffeaarabica. abotic factors in coffee agroforestry show soil moisture 18.3%, air humidity 60 - 75%, soil pH Â 7.3, soil temperatureÂ 21 Â° C, air temperature 21 - 25 Â° C, light intensity Â 877 lux, and altitude ranges from 906 - 934 m asl.Keywords: allometric, coffee, agroforestry, abiotic factors, carbonABSTRAKSistem agroforestri merupakan solusi yang ditawarkan agar luas hutan tidak semakin berkurang akibat kerusakan hutan dan lingkungan mampu melakukan fungsinya yakni sebagai penyimpan karbon. Penelitian ini bertujuan untuk mengetahui potensi karbon tersimpan pada tegakan kopi dan faktor abiotik pada tegakan kopi di lahan agroforestri. Pemilihan sampel tegakan kopi secara purposive sampling, tiap sampel tegakan Coffea arabica, Coffea canephora, dan Coffea liberica berjumlah 20 pohon dengan jumlah total sampel 60 tegakan. Faktor abiotik diukur pada tiga titik representatif. Data yang diperoleh berupa dbh (Â±1,3 m), spesies kopi, umur tanaman, berat jenis kayu,data faktor abiotik, biomassa, dan karbon. Analisis data perhitungan biomassa meliputi rumus allometrik Ketterings berat kering = 0,11 Ï D2,62 Â (2001) dan rumus allometrik Arifin berat kering = 0,281 D2,0635(2001). Analisis data biomassa karbon = berat kering x 0.47. Hasil penelitian menunjukkan simpanan karbon terbesar terdapat pada Coffea liberica, kemudian Coffea canephora dan simpanan karbon paling kecil pada Coffea arabica. faktor abotik di agroforestri kopi menunjukkan kelembaban tanah 18.3%, Kelembaban udara 60 - 75%, pH tanah 7,3, Suhu tanah 21Â°C, suhu udara 21 - 25Â°C, intensitas cahaya 877 lux dan ketinggian tempat berkisar 906 â€“ 934 m dpl.Kata kunci: allometrik, kopi, agroforestry, faktor abiotic, karbon